Modification of water retention and rheological properties of fresh state cement-based mortars by guar gum derivatives. (30th September 2016) - Govin, Alexandre; Bartholin, Marie-Claude; Biasotti, Barbara; Giudici, Max; Langella, Valentina; Grosseau, Philippe
Highlights: Effect of chemical composition and structure of guar gum on fresh mortar properties was examined. Effect of molar substitution and degree of substitution of hydrophobic units was investigated. Increasing MSHP leads to an improvement of the water retention and the stability of mortars. Alkyl chains promote water retention and increases the resistance to the flow of admixed mortars. Abstract: The present study examines the influence of chemical composition and structure of guar gum derivatives on water retention capacity (WR) and rheological behavior of fresh state cement-based mortars. The investigation was also completed by adsorption isotherms. For this, original guar gum, three HydroxyPropyl Guars (HPG) and two hydrophobically modified HPGs were selected. The effect of the molar substitution (MSHP ) and of hydrophobic substitution (DSAC ) was investigated. The results highlight that chemical composition of HPGs has a remarkable effect on fresh state properties of mortars. The original guar gum does not impact on neither WR nor rheological behavior. Increasing MSHP leads to an improvement of the WR and the stability of mortars while the hydrophobic units further enhance WR and lead to a decrease in the yield stress and an increase in the resistance to the flow of admixed mortars.